Overview of European Legislation For Digital Copyright Protection: Towards a Competitive Knowledge-Based Economy: European Legislation for Digital Copyright Protection (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Digital technologies are becoming more importantin business and a potential locomotive for economic growth and trade. The U.Sproducers and consumers have enjoyed a ‘Digital revolution’ since 1990’s and itis not surprising that they became the largest economy in the informationsociety. Although following developments in information society one step behindthe U.S, the challenge for Europe is to clinch the digital age and become themost competitive knowledge-based economy and society is the new goal of the EU. Statistics shows that, in Europe 90% of firms and most of their employeeshave an Internet connection 60% of those firms have web sites and  approximately 20%  of  the European  companies  sell and  buy  over through the Internet .